Identification of 7-HOCA as a Potential Biomarker in Glioblastoma: Evidence from Genome-Wide Association Study and Clinical Validation - Zhao Z; Xing N; Sun G (International Journal of General Medicine)
Zhenxiang Zhao,1 Na Xing,2 Guozhu Sun3 1Department of Neurosurgery, The Fourth Hospital of Hebei Medical University, Shijiazhuang, 050000, People’s Republic of China; 2Department of Endocrinology, The Fourth Hospital of Hebei Medical University, Shijiazhuang, 050000, People’s Republic of China; 3Department of Neurosurgery, The Second Hospital of Hebei Medical University, Shijiazhuang, 050000, People’s Republic of ChinaCorrespondence: Guozhu Sun, Department of Neurosurgery, The Second Hospital of Hebei Medical University, No. 215, Heping West Road, Shijiazhuang, Hebei, 050000, People’s Republic of China, Email Sungzh705@hebmu.edu.cnPurpose: Glioblastoma (GBM) is associated with metabolic disturbances, yet the relationships between metabolites with GBM have not been comprehensively explored. This study aims to fill this gap by integrating Mendelian randomization (MR) analysis with clinical validation.Patients and Methods: Summary data from genome-wide association study (GWAS) of cerebrospinal fluid (CSF) metabolites, plasma metabolites, and GBM were obtained separately. A total of 338 CSF metabolites and 1400 plasma metabolites were utilized as exposures. Concurrently, GBM was designated as the outcome. A two-sample bidirectional MR study was conducted to investigate the potential association. The inverse variance weighted (IVW) analyses were conducted as causal estimates, accompanied by a series of sensitivity analyses to evaluate the robustness of the results. Additionally, metabolite levels in clinical plasma and CSF samples were quantified using liquid chromatography-mass spectrometry to validate the findings.Results: MR analysis identified eight CSF metabolites and six plasma metabolites that were closely associated with GBM. Among these, elevated levels of 7-alpha-hydroxy-3-oxo-4-cholestenoate (7-HOCA) in both CSF and plasma were found to promote GBM. In terms of clinical validation, compared to the control group, 7-HOCA levels were significantly higher in both the CSF and plasma of GBM group.Conclusion: This study provides a comprehensive analysis of the metabolic factors contributing to GBM. The identification of specific metabolites, particularly 7-HOCA, that have vital roles in GBM pathogenesis suggests new biomarkers and therapeutic targets, offering potential pathways for improved diagnosis and treatment of GBM.Keywords: 7-alpha-hydroxy-3-oxo-4-cholestenoate, metabolite, glioblastoma, cerebrospinal fluid, Mendelian randomization, plasma